The Effect of Teacher-Provided Rewards on the Discipline of Group B Children at TK Ar Rehan Pekanbaru - Puspita, Yenda; Efastri , Sean Marta; Suharni, Suharni; Wilyanita , Nopa (Educative: Jurnal Ilmiah Pendidikan, 2026)
This study is motivated by the relatively low level of discipline among early childhood learners, which necessitates effective strategies to foster positive behavior in classroom settings. The purpose of this research is to examine the effect of teacher-provided rewards on the discipline of Group B children at TK Ar Rehan Pekanbaru. This study employed a quasi-experimental design with a nonequivalent control group, involving an experimental group and a control group. Data were collected through observation and documentation using a systematically developed discipline observation sheet. Data analysis was conducted to identify changes within each group and differences between the two groups. The findings indicate that teachers' use of rewards has a significant positive effect on children’s discipline. The group receiving the intervention demonstrated greater improvement in disciplined behavior compared to the group without the intervention. These results highlight the importance of rewards as a form of positive reinforcement in shaping disciplined behavior in early childhood education. This study contributes to strengthening the use of positive reinforcement-based instructional strategies that teachers can effectively implement to support optimal character development in young children.